The political economy of AI: a content analysis of ChatGPT outputs and anti-Palestinian media bias - King, Gretchen (2026)
Palestine represents a site of digital occupation and a laboratory for the Israeli military–industrial–communications complex that entails collaboration between Israeli military, technology and academia. Considering the current popularity of generative artificial intelligence (AI) and the use of AI in the genocide in Palestine, we investigate how generative AI platforms like ChatGPT are biased towards Palestinians, and how prompting in English and Arabic produces different biases towards Palestinians. A theoretical framework for analysing digital Orientalism is advanced through a historicisation of media imperialism, the military–industrial–communications complex and the political economy of AI in occupied Palestine. Grounded in research-based teaching methods, and employing a mixed-method content and frequency analysis and comparison of ChatGPT outputs in English and Arabic, this article expands research on AI biases, algorithmic oppression and digital divides within the context of digital Orientalism and anti-Palestinianism. We document an anti-Palestinian bias in AI-generated content in English and Arabic that is evident through biased language and the omission of historical and legal contexts, Palestinian human rights, Palestinians’ status as refugees and their right of return. ChatGPT-generated outputs reproduced Orientalist discourse and Israeli narratives entailing Nakba denial, further emphasising the urgency for critical digital media literacy on AI.